Biocompatible microgel-modified electrospun fibers for zinc ion release. (20th March 2015) - Wilke, Philipp; Coger, Vincent; Nachev, Milen; Schachschal, Susann; Million, Nina; Barcikowski, Stephan; Sures, Bernd; Reimers, Kerstin; Vogt, Peter M.; Pich, Andrij
Abstract: We present a novel and facile method for the design of biocompatible microgel-modified microfibers loaded with ZnO nanoparticles capable of zinc ion release under physiological conditions. The microfibers consist of three materials hierarchically assembled in a controlled and reproducible way. We synthesized poly( N -vinylcaprolactam-co-itaconic acid) aqueous microgels with carboxylic groups located in the microgel core. The obtained microgels can be loaded with various amounts of ZnO nanoparticles by in-situ growth of ZnO in microgels. As shown by electrophoretic mobility and TEM measurements, ZnO nanoparticles are selectively loaded in the microgel core and stabilized by itaconic acid groups bearing strong negative charges. ZnO-loaded microgels were used as functional additive to produce poly(ε-caprolactone) (PCL) microfibers using the electrospinning process. The resulting microfibers consist of a PCL core coated with the microgels located at the surface of the fibers. The variation of the ZnO amount loaded into microgels allows regulating the ZnO content in microfibers and gives the possibility to tune the released amount of zinc ions in aqueous medium at pH 7.5 and 37 °C. We demonstrate that the obtained functional microfibers are biocompatible and non-toxic, thus being good candidates for biomedical applications like scaffolds for tissue engineering, biointerface coatings or wound closing dressings. Graphical abstract: Highlights: Novel functional, biocompatible microfibers have been developed. Microfiber surface was modified by microgels, loaded with ZnO NPs, during electrospinning process. Microfiber pads are capable of zinc ion release under physiological conditions.